An Introduction to Metabolic and Cellular Engineering - Cortassa, Sonia (World Scientific, 2002)
Metabolic and cellular engineering, as presented in this book, is a powerful alliance of two technologies: genetics â€" molecular biology and fermentation technology. Both are driven by continuous refinement of the basic understanding of metabolism, physiology and cellular biology (growth, division, differentiation), as well as the development of new mathematical modeling techniques. The authorsâ€TM approach is original in that it integrates several disciplines into a coordinated scheme, i.e. microbial physiology and bioenergetics, thermodynamics and enzyme kinetics, biomathematics